Assessing the recovery of dodecanol from alkyl polyglycosides (APG) using solvent extraction - Zulkifly, Jemaat; Mahadhir, Muhammad; Hairul Nizam, Abdul Rani (Elsevier Ltd, 2023)
Dodecanol, known as lauryl alcohol, is commonly used in the production of alkylpolyglycosides (APG) by reacting dextrose with an excess of dodecanol in the presence of an acid catalyst. After the reaction is completed, the challenging part is the purification step, to separate unreacted dodecanol from APG to ensure the final product meets an industrial specification requiring less than 5% of the dodecanol residue. Current separation methods i.e., evaporation and distillation, require high energy and could deteriorate the product quality if it is not operated carefully. In this research, the extraction process was evaluated to separate the unreacted dodecanol without compromising the quality of the final product. The study investigates the effect of the solvent matrix, temperature and stirring speed for the extraction of dodecanol using a mixture of water with ethanol, propanol or toluene as a solvent matrix. The composition ratio of sample: solvent: water was fixed at 10:10:10 (in mL). The extraction temperature was manipulated between 60 °C and 80 °C and stirring speed was at 5 and 7 rpm. In addition, the extraction was also subjected to the ultrasonic frequency set at 9 Hz for 30 min and using toluene as a matrix solvent. Results show that higher extraction yield was obtained at low temperatures and stirring speed. By using a solvent matrix-toluene leads to the highest extraction yield of 15.02 w/w%. Applying ultrasonic during the extraction process increased the extraction yield to 32 w/w%, indicating that the ultrasonic has intensified the extraction process. In conclusion, the excess of dodecanol in the APG sample could be separated via an extraction process. This potential method allows an alternative separation technique at a low investment cost, energy saving and eventually meeting the APG’s product specifications requirement.